입원아동 돌봄을 위한 가족중심 순회의 통합적 고찰 - 임미해; 오진아; Im, Mihae; Oh, Jina (Child health nursing research, 2016)
Purpose: Involvement of families in rounds is one strategy to implement patient- and family-centered care to help families get clear information about their child, and be actively involved in decision making. The purpose of this paper was to identify the major concepts of family-centered rounds for hospitalized children. Methods: We searched five electronic databases for relevant articles and used Whittemore and Knafl's integrative review methods to synthesize the literature. Articles published between June 2003 and January 2016 were reviewed and through full text screening 24 peer-reviewed articles were found that met the selection criteria for this review. Results: Through in-depth discussion and investigation of the relevant literature, four overarching components emerged: (a) cognition of parents and medical staff, (b) effective communication, (c) collaboration of family and medical staff, (d) coaching of medical staff. Conclusion: For successful family-centered rounds positive cognition is important. Appropriate communication skills and consideration of multi-cultural family can lead to effective communication. Offering consistent and transparent information is important for collaboration between family and medical staff. Prior education on family-centered rounds is also important. Four major components have been identified as basic standards for implementing family-centered rounds for hospitalized children.